Development of Non-Point Source Pollution Model for Maize Cultivation Under Tropical Condition - Rusnam, (2006)
Land development activities contibute to water quality impairment. The use of models plays an important role in the assessment of diffuse pollution sources and their delivery to the receiving water bodies. Pollutant export equations or event mean concentration (EMC) values are the basic requirement for storm water quality assessment and control. This is not yet available for tropical areas such as the Malaysian enviroment. This research project was carried out at the Precision Agriculture Experimental Plot in Universiti Putra Malaysia (UPM). It is located at latitude 3º 02’ N and longitude 101º 42’ E, with 31 m above mean sea level. The soil in the study is Serdang series and the crop grown in the 0.56 ha area was maize (Zea Mays). The plot was isolated from the surrounding areas by building perimeter bunds to protect from runoff produced by the adjacent areas. Rainfall is mainly the driving force for non-point source (NPS) pollution. Therefore, the daily rainfall data was collected and analysed to study the distribution of daily rainfall from 1985 to 2003. Twenty rain events in crop season I, nineteen events in crop season II and eight in crop season III were monitored to calculate the EMC (event mean concentration) values of the parameters which contributed mostly from the NPS pollution. The median EMC values for BOD, COD, NO3, TKN, TP, TSS and Turbidity were calculated to be 10.3, 101.2, 1.1, 2.6, 0.7, 1027.1 mg/L and 879.4 NTU in crop season I, 9.0, 88.1, 1.0, 2.1, 0.5, 867.8 mg/L and 856.2 NTU in crop season II and 10.5, 102.5, 0.5, 1.1, 2.6, 0.7, 950.8 mg/L and 886.5 NTU in crop season III, respectively. From the correlation study, it was observed that EMC values were significantly related to runoff quantity, dry period between the storm events and the day after fetilizer application. Multiple regression analyses among these four parameters were conducted to determine regression models for the selected pollutants. There was no significant difference between observed and model data for all parameters, after calibration and validation. In can be concluded that prediction key by the regression model was satisfactory and can be applied to agricultural areas of similar characteristics. These pollutant export equations would be useful to predict EMC values and NPS pollution loading under tropical condition. First flush phenomenon was analyzed for selected parameters. The strongest first flush phenomenon was observed for Total Suspended Solid (TSS), where about 60% of pollutant mass (load) could be captured by isolating 42% of runoff volume. Other parameters exhibited weak and closed to uniform. The existing Water Quality Index (WQI) proposed by the Department of Enviromental (DOE) Malaysia was reviewed and found to have a few limitations when applied to agricultural areas. A runoff quality index (RQI) was proposed to assess the runoff quality an agricultural area such as a maize field, which includes Total Kjeldhal Nitrogen (TKN) and Total Phosporous (TP).